Beta Saham dan Return Saham Pada Sektor IDXENERGY - Saleh, Dean Subhan; Hendriani, Maria; Fajri, Nikita Nurul (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This study aims to analyze the effect of the quick ratio, long term debt to equity ratio, tobin's q, inflation and world oil prices on IDXENERGY stock returns with stock beta as the intervening variable. The research sample consisted of 29 companies using purposive sampling. This research is a quantitative study using panel data regression analysis and path analysis using Eviews 13. Partial results show that quick ratio and LTDER have no effect on stock beta, while Tobin’s Q and inflation have a significant effect on stock beta. Quick ratio and LTDER have no effect on stock returns, while Tobin’s Q, inflation, world oil prices and stock beta have a significant effect on stock returns. Simultaneously quick ratio, LTDER, Tobin’s Q, inflation and world oil prices affect stock beta and simultaneously quick ratio, LTDER, Tobin’s Q, world oil prices and stock beta affect stock returns. In addition, stock beta is able to mediate Tobin’s Q and inflation on stock returns but is unable to mediate quick ratio, LTDER and world oil prices on stock returns. Simultaneously stock beta is able to mediate quick ratio, long term debt to equity ratio, Tobin’s Q, inflation and world oil prices on stock returns.